Lesbian potentiality and feminist media in the 1970s - Samer, Rox (Duke University Press, 2022)
In Lesbian Potentiality and Feminist Media in the 1970s, Rox Samer explores how 1970s feminists took up the figure of the lesbian in broad attempts to reimagine gender and sexuality. Samer turns to feminist film, video, and science fiction literature, offering a historiographical concept called “lesbian potentiality”—a way of thinking beyond what the lesbian was, in favor of how the lesbian signified what could have come to be. Samer shows how the labor of feminist media workers and fans put lesbian potentiality into movement. They see lesbian potentiality in feminist prison documentaries that theorize the prison industrial complex’s racialized and gendered violence and give image to Black feminist love politics and freedom dreaming. Lesbian potentiality also circulates through the alternative spaces created by feminist science fiction and fantasy fanzines like The Witch and the Chameleon and Janus. It was here that author James Tiptree, Jr./Alice B. Sheldon felt free to do gender differently and inspired many others to do so in turn. Throughout, Samer embraces the perpetual reimagination of “lesbian” and the lesbian’s former futures for the sake of continued, radical world-building.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; cinéma; communication; discipline; histoire et politique; lesbianisme; personnes lesbiennes; périodes historiques; ressource en ligne; thématiques; études littéraires

Imaginary women, imaginary audience: Gender and top 40 radio in Montréal - Maki, Christine (Women in radio: Unfiltered voices from Canada, 2020)
Though they no longer call themselves Top 40, popular music radio stations remain present on the dial today, complete with loud, mostly male DJs, hoping to attract a mainly female audience. Using the talk on two Montréal music stations, which hire mainly male announcers who select music assumed to fit women’s tastes, Christine Maki examines the continuing perception that women’s voices aren’t low or authoritative enough and that emotional issues prevent them from presenting difficult news stories. Her conclusion: the overall medium remains relatively unchanged over the decades, despite massive evolution in the wider media landscape.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; communication; culture populaire; discipline; discours dominant; genre; montréal; périodes historiques; radio; ressource en ligne; régions géographiques; sexisme; stéréotypes de genre; systèmes d'oppressions